Genome-wide SNPs detection by genomic comparison between Dongxiang wild rice (Oryza rufipogon) and cultivated rice Nipponbare (Oryza sativa ssp. japonica). Issue 4 (26th July 2017) - Zhang, Meng; Huang, Wenyang; Xia, Zijun; Liu, Jiahui; Xie, Jiankun; Zhang, Fantao
Abstract: Dongxiang wild rice ( Oryza rufipogon, DXWR) exhibits valuable agronomic traits and represents a precious germplasm resource for rice breeding. The use of genetic markers can greatly speed up the breeding process and facilitate research on genetics and genomics. In our previous study, we identified insertion–deletion polymorphisms between DXWR and cultivated rice Nipponbare ( Oryza sativa ssp. japonica ), using whole-genome sequencing in DXWR. In this study, to further explore the genetic variations and enrich the available genetic markers of DXWR, we identified 1, 089, 478 single-nucleotide polymorphisms (SNPs) (corresponding to one SNP per 0.33 kb of the genome) by genomic comparison between DXWR and Nipponbare, using the genome sequencing data and bioinformatics approaches. Furthermore, the accuracy of the identified SNPs was also validated by polymerase chain reaction amplification and Sanger sequencing. This genome-wide SNPs identification greatly increases the number of genetic markers available for DXWR and provides new opportunities to exploit this valuable and endangered germplasm resource.